A large-update primal–dual interior-point algorithm for second-order cone optimization based on a new proximity function. (2nd July 2016) - Fathi-Hafshejani, S.; Mansouri, H.; Peyghami, M. Reza
Abstract : In this paper, we propose a large-update primal–dual interior-point algorithm for second-order cone optimization (SOCO) based on a class of kernel functions consisting of a trigonometric barrier term. The algorithm starts from a strictly feasible point and generates a sequence of points converging to an optimal solution of the problem. Using a simple analysis, we show that the algorithm has worst case iteration complexity for large-update primal–dual interior point methods which coincides with the so far best-known iteration bound for SOCO.